The Description Of Nurses’ Spiritual Support For Patients Of Different Religions In Hospitals - Pattinasarany, Injilina Luzia Janetha; Ranimpi, Yulius Yusak; Pilakoannu, Rama Tulus (Jurnal Keperawatan Soedirman, 2021)
The term spiritual is an inseparable part of the meaning of religion. In the health service, providing spiritual support is a duty of health workers, especially nurses. Social conflicts that lead to religious conflict, may affect nurses' performance, especially to fulfill patients' spiritual needs with different religions or beliefs. This makes studies related to nursing and religion are impressive. This study aimed to describe nurses' spiritual support for patients of other religions in hospitals. The research used a qualitative method with a phenomenology study approach. The data collection was performed using interviews. The informant selection technique used the purposive sampling technique and resulted in 5 informants. According to Creswell, the trustworthiness used triangulation, while the data analysis method used a method. Six themes emerged from this study, including the meaning of God, the meaning and the purpose of life, source of happiness, the meaning of the tragic event, assessment of good and bad things, and the interaction between nurses and patient with same or different religions. The conclusion of this study is the spiritual support provided by nurses as an informant is focus on two things, namely the meaning of God's existence and relationships with others.